Extracellular vesicles display distinct glycosignatures in high-grade serous ovarian carcinoma - Kristina Mae Bienes; Akira Yokoi; Masami Kitagawa; Hiroaki Kajiyama; Morten-Thaysen Andersen; Rebeca Kawahara (BBA Advances)
High-grade serous ovarian carcinoma (HGSOC) is a deadly subtype of ovarian cancer (OC), often diagnosed at late stages due to nonspecific symptoms and lack of effective markers for early detection. Aberrant protein N-linked glycosylation has been reported in HGSOC, holding a potential for improving the diagnosis and prognosis of affected patients. Building on our recent observation documenting that HGSOC-derived extracellular vesicles (EVs) exhibit aberrant protein expression patterns, we here explore the protein N-glycosylation displayed by EVs isolated from HGSOC cell lines and patient ascites relative to those from matching controls to unveil candidate markers for HGSOC. Comparative glycoproteomics of small EVs (sEVs, <200 nm) and medium/large EVs (m/lEVs, >200 nm) isolated from HGSOC and non-cancerous cell lines revealed lower overall N-glycosylation of EV proteins and a decreased protein expression of oligosaccharyltransferase (OST) subunits from HGSOC compared to non-cancerous cell lines. Increased α2,6-sialylation was also observed in m/lEVs from HGSOC cell lines and patient ascites by lectin blotting, which correlated with increased gene expression of ST6GAL1 and decreased gene expression of ST3GAL3/4 in HGSOC compared to normal ovary tissues. Our study provides insights into the EV glycoproteome of HGSOC and the underlying changes in the glycosylation machinery in HGSOC tissues, opening new avenues for the discovery of novel markers against HGSOC.